Decentralizing the Chilean miracle: regional intergenerational mobility in a developing country. Issue 5 (4th May 2023) - Orihuela, Javier Cortés; Díaz, Juan D.; Cubillos, Pablo Gutiérrez; Montecinos, Alexis; Troncoso, Pablo A.; Villarroel, Gabriel I.
ABSTRACT: We estimate spatially disaggregated measures of intergenerational mobility in Chile through an administrative dataset linking children's and their parents' earnings from the formal private labour sector. We report remarkable heterogeneity as we find higher and lower upward mobility in mining and agricultural regions, respectively, corroborating previous findings by Connolly et al. in 2019 with the distinction that Chile is a unitary state, implying that factors other than institutional differences shape mobility.